Association between Serum Thyroid Hormones and Fatty Liver Disease - Vahedi 1, Hamid; Ganghorban 2, Maryam; Zolfaghari 3, Pouneh; Nagafi 4, Ali; Ebrahimi 3, Rouya; Sohrabi 5*, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2019)
Background: Non-alcoholic fatty liver disease is one of the most common chronic liver diseases. Given the lack of definitive documentation for the effect of thyroid gland disorders on fatty liver, this study was conducted to determine the relationship between serum thyroid hormones levels and fatty liver in patients referring to Imam Hossain Hospital in Shahroud, in 2016.Methods: This case-control study was performed on 150 patients. The case group consisted of fatty liver patients whose disease was diagnosed based on laboratory and ultrasound findings, and a control group of patients with any other diseases without fatty liver. After liver ultrasonography, blood samples were taken from all patients and thyroid hormones levels were measured.Results: Of the 150 patients examined, the mean BMI of the patients was 24.79±6.9 kg / m2, which was significantly higher in the case group (P<0.012). The mean FBS level, was 131.5±83.5 mg / dl, which was significantly higher (P<0.001) in the case group. Similarly, the mean of TG was 245.5±128.5 mg / dl, which was significantly higher in the case group (P<0.047). On the other hand, the mean LDL of patients was 145.5±30.5 mg / dl, which was significantly higher (P<0.012) in patients with fatty liver. Further, the mean TSH of patients was significantly higher in the case group (P<0.014). Finally, there were no significant differences between the two groups regarding other variables.Conclusions: The results of this study suggested that thyroid gland disorders, especially hypothyroidism, were significantly higher in patients with fatty liver than in other patients. Nevertheless, they could not be influential in the incidence, exacerbation and persistence of fatty liver as a favorable factor.